Transformasi Digital Kabupaten Nganjuk melalui Strategi Penerapan Sistem Pemerintahan Berbasis Elektronik (SPBE) - Ajie Hanif Muzaqi (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
The Electronic-Based Government System (SPBE) serves as a foundational pillar for driving digital transformation in public administration by integrating information and communication technology (ICT) to ensure governance that is efficient, transparent, participatory, and accountable. The implementation of SPBE requires not only the institutional readiness of government bodies but also strategic collaboration with the private sector, technology communities, and the public as end-users of digital services. This study aims to analyze the strategies for implementing SPBE in Nganjuk Regency using a mixed-methods approach. This approach combines qualitative descriptive analysis to identify internal and external factors influencing implementation, along with a weighted and scored SWOT analysis to formulate more measurable strategic recommendations. Data were collected through field observations, in-depth interviews with key stakeholders, documentation review of regulations and performance reports, and questionnaires to capture the perceptions of both civil servants and the community. The findings indicate that Nganjuk Regency possesses substantial strengths and opportunities to accelerate digital transformation, although challenges remain, particularly related to disparities in human resource competencies and the need for stronger service integration across sectors. Based on the SWOT analysis, the study proposes four primary SO strategies: (1) promoting the Regent’s commitment through the “Digital Ambassador” program to enhance digital literacy and adoption among younger generations; (2) strengthening the Regent’s role as a digital influencer in promoting electronic public services; (3) improving and expanding digital services with policy support and technical assistance from the central government; and (4) enhancing the competencies of civil servants through collaboration with academic institutions, technology communities, and other strategic partners. Collectively, these strategies are expected to accelerate SPBE implementation and improve the quality of public services in Nganjuk Regency on a sustainable basis.